High risk of coagulopathy among Type-2 Diabetes Mellitus clients at a municipal hospital in Ghana - Ephraim, R.K.D.; Awuku, Y.A.; Adu, P.; Ampomah, L.T.W.; Adoba, P.; Panford, S.; Ninnoni, J.P.K.; Agbodzakey, H. (Ghana Medical Journal, 2017)
Background: Persistent hyperglycaemia in diabetes mellitus causes coagulopathies due to glycation of haemoglobin, prothrombin, fibrinogen and other proteins involved in the clotting mechanism. Shortened activated partial thromboplastin time (APTT) and prothrombin time (PT) reflect hypercoagulable state, which is associated with an increased thrombotic risk and adverse cardiovascular effects. This study assessed the coagulation profile of type 2 diabetes mellitus (T2DM) clients at a municipal hospital in Ghana. Methods: A hospital-based case-control study was conducted from January to April 2015 at the Agona Swedru Municipal Hospital. Sixty (60) persons with T2DM and 40 without were recruited and screened using appropriate protocols. Blood samples were collected for coagulation and biochemical tests. Demographic and clinical information were collected using pre-tested questionnaire. Data was analyzed with GraphPad Prism version 5. Results: APTT and PT were significantly shorter among patients with T2DM compared to those without (20.88 ± 5.19 v 31.23 ± 5.41, P=0.0001; and 11.03 ± 2.06sec v 14.46 ± 1.86, P=0.0001 respectively). INR was decreased among patients with T2DM compared to those without (0.83 ± 0.18 v 1.13 ± 0.17, P=0.0001). No significant difference was found in platelet count between T2DM and non-diabetics (179.85 ± 66.15×103 /mm3 v 168.55 ± 35.77×103 /mm3, P=0.326). Serum magnesium was lower among the T2DM patients compared to the non-diabetics, while serum ionized calcium was significantly higher among the T2DM patients (P<0.05). Conclusion: Clients with T2DM may have a high coagulation risk evidenced by shortened APTT, PT and a high ionized calcium compared with controls.
Journal Article on High risk of coagulopathy among Type-2 Diabetes Mellitus
Keywords: Type 2 Diabetes Mellitus; coagulation; prothrombin time; activated partial thromboplastin time; ionized calcium